Country image of gastronomy and branding Hawker Culture: local consumers' perception - Kim, Bona; Lee, Derrick C.H.; Chua, Bee-Lia; Han, Heesup (Elsevier, 2022)
This study examined local food diners' perceptions of gastronomy—composed of food, country image, and culture—in Singapore, a city-state. This study successfully identified the country image associated with gastronomy by adopting the concept of UNESCO Creative Cities of Gastronomy and explored the impact of country image on the local diners' perception of Hawker Culture as a country brand, based on the brand resonance model. Image factors (food outlets and restaurants, food activities, education and training, and local ingredients and cooking skills) were explored. The perceived facets of the country were linked to awareness, which in turn stimulated the love for Hawker Culture in forming loyalty. This research provides discernments to rejuvenate and promote Singapore as a UNESCO Creative City of Gastronomy, which will pave the way for the continuous support of Hawker Culture from residents as a notable cultural icon.